Centropontine Myelinolysis Related to Refeeding Syndrome in an Adolescent Suffering from Anorexia Nervosa - Leroy, Sandrine; Gout, Ariel; Husson, Beatrice; de Tournemire, Renault; Tardieu, Marc (Neuropediatrics, 2012)
Centropontine myelinolysis (CPM) is a rare neurologic disorder defined by symmetric demyelination in the central pons, mostly due to alcoholism, malnutrition, or water-electrolyte abnormalities. We report an unusual case of CPM likely due to hypophosphatemia, related to a refeeding syndrome in the context of mental anorexia. A 15-year-old girl with mental anorexia presented with hypophosphatemia in the following days of enteral refeeding, and then suffered from confusion, neurological signs, and typical MRI lesions of CPM. Hypophosphoremia may be considered as a causative agent in CPM related to refeeding syndrome. This clinical observation also highlights the importance of recognizing patients at high risk of refeeding syndrome to initiate a balanced nutrition with careful monitoring.
Keywords: central pontine myelinolysis; children; electrolyte; refeeding syndrome; mental anorexia